PENINGKATAN KOMPETENSI PERAWAT DALAM PENERAPAN PROSEDUR PHOTOTHERAPY INTERVENTION MELALUI METODE PEMBELAJARAN DRILL - Febrianti, Urai Ririn Indah; Suhariyanto, Suhariyanto; Baedlawi, Azhari; Kapadia, Raju (Coping: Community of Publishing in Nursing; Vol 11 No 1 (2023): Februari 2023DO - 10.24843/coping.2023.v11.i01.p08, 2023)
The role of nurses is needed to prevent unwanted side effects during phototherapy intervention is carried out by ensuring the accuracy of carrying out the procedure of phototherapy intervention which contains the sequence of the process of performing nursing actions from beginning to end. Health workers are required to have the knowledge and skills to be able to provide appropriate nursing care at the time of phototherapy intervention implemented. The drill method is used to prevent unexpected events (PUE) such as hyperthermia, hypothermia, and burns during phototherapy intervention. The purpose of this study was to determine the effect of the drill method on the knowledge and skills of nurses in the implementation of phototherapy intervention procedures. The type of research used is pre-experimental with pre-post test without control group, through the implementation of the drill learning method for 2 weeks as many as 17 nurses of RSUD dr. Rubini. Research instrument characteristics of respondents, knowledge, and observation skills of nurses. Data analysis test using Paired T-Test Test used on knowledge and Wilcoxon test for skills. The value of pre-test nurse skills of 15,65 and post-test value of 25,47 so as to obtain an increase in skills of 9,82 with p value of 0,000 < 0,05. There is an effect of drill method on knowledge with pre test value of 64,7012 and post test value of 88,4288 resulting in an increase in knowledge of 23,7276 with a value of p = 0,000. Learning the drill method with the phototherapy intervention learning module gives the impact of increasing knowledge and skills competence continuously. The results of this study successfully proved that there is an effect of the drill method to increase the knowledge and skills of nurses in the implementation of phototherapy intervention procedures.